The influence of self-efficacy, perceived value, student engagement and competition preparedness of outstanding student election delegates (Pilmapres) in LLDIKTI Region III DKI Jakarta in 2024 - Maulida, Ahmad Fikron (Priviet Social Sciences Journal, 2026)
This study examines the competition readiness of students participating in the Pemilihan Mahasiswa Berprestasi (Pilmapres) competition under LLDIKTI Region III Jakarta. While earlier research concentrated on career impact and selection tools, this study highlights factors related to student readiness prior to the competition. Data were gathered from 63 participants representing 37 universities between 2021 and 2024 using a quantitative approach and an online survey. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for the analysis. The results show that perceived value, student engagement, and competition readiness were not significantly affected by self-efficacy. However, perceived value positively impacted both competition readiness and student engagement. Furthermore, although it did not mediate the relationship between preparedness and self-efficacy, student engagement significantly improved competition readiness. These results imply that perceived value is a more important factor than self-efficacy in promoting student engagement and preparedness.  The intricacy of Pilmapres may necessitate more thorough preparation techniques than just faith.  This study advances the knowledge of student development strategies in competitive academic environments and provides insightful information about the variables affecting students' competition readiness.